PENGARUH AL-FATIHAH REFLECTION THERAPY (ART) UNTUK MENINGKATKAN BERPIKIR POSITIF SISWA MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 5 PEKANBARU - Yanda, Okta Nila; Umari, Tri; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aimed of this study was to determine the differences in positive thinking before and after applying Al-Fatihah Reflection Therapy (ART) and to know the effect of Al-Fatihah Reflection Therapy (ART) to improve students' positive thinking. The study was conducted at SMA Negeri 5 Pekanbaru on 8 subjects with a purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The data collection used is a positive thinking questionnaire adapted from Albrecht (1994). The results showed that there were differences in the way students thought before and after being given Al-Fatihah refection therapy (ART) with a significance value of 0.012 <0.05. In addition, based on the Spearman rank test seen that there is a significant effect between Al-Fatihah reflection therapy (ART) on positive thinking of students with a significance value of 0.039 <0.05. The effect of ART reflection on students' positive thinking was 52.27% while 47.73% was influenced by other factors that came from within and from the student's environment. From the results obtained, it is recommended that educational institutions should continue to carry out activities that can improve the IMTAQ process such as relaxation, dzikir or religious teaching / learning to encourage the development of more positive thoughts, perceptions, insights and attitudes.Key Words: Al-Fatihah Reflection Therapy (ART), Group Guidance, Positive Thinking